Contribution of groundwater to the outflow from ungauged glacierized catchments: a multi‐site study in the tropical Cordillera Blanca, Peru. Issue 11 (3rd December 2014) - Baraer, Michel; McKenzie, Jeffrey; Mark, Bryan G.; Gordon, Ryan; Bury, Jeffrey; Condom, Thomas; Gomez, Jesus; Knox, Sara; Fortner, Sarah K.
Abstract The rapid retreat of the glaciers of the Cordillera Blanca is having a noticeable impact on the downstream hydrology. Although groundwater is a critical hydrologic component that sustains stream flows during the dry season, its characteristics and its contribution to downstream hydrology remain poorly understood. In this study, we analyse the hydrochemical and isotopic properties of potential hydrologic sources mixing in surface streams to characterize the proglacial hydrology in four glacially fed watersheds within the Cordillera Blanca, Peru. Water samples from streams, glacial melt and groundwater were collected in 2008 and 2009 and analysed for major ions and stable isotopes (δ18O and δ2H). Multivariate analysis of variance was used first to identify the hydrochemical and isotopic characteristics (tracers) of the water samples that depend primarily on the water source. Then several analyses, including hierarchical cluster analysis and mixing diagrams, were performed using these source‐dependent tracers, enabling a qualitative description of the key hydrological mechanisms that characterize the study watersheds. Finally, we applied a multi‐component spatial mixing model, the hydrochemical basin characterization method, to quantify the contributions of different water sources to the outflow from the four watersheds. The hydrochemical basin characterization method results show that groundwater is a major component of the discharge during the dry season and that the groundwater contribution to outflow is greater than 24% in all of the valleys. The results are used to develop a conceptual proglacial hydrological model of the Cordillera Blanca valleys. Talus and avalanche cones are identified as key components of the hydrology of the valleys. The talus deposits collect precipitation and runoff from higher elevations (approximately 400 m above the valley floor) and have a residence time that is long enough to actively release substantial volumes of water throughout the dry season. Copyright © 2014 John Wiley & Sons, Ltd.